UJI ADAPTASI GALUR PADI (Oryza sativa L.) PADA LAHAN SALIN DI KAMPUNG BOKEM DISTRIK MERAUKE - Nofila F Rumaikewy; Rosmala widijastuti; Diana S Susanti; A A Limbongan; Abdullah Sarijan (Musamus University, 2023)
This study aims to analyze the adaptability of 2 new lines of rice tested in saline soils. This research was carried out for 3 months, from June to August 2018, in Bokem Village, Merauke District. This study used a randomized block design (RBD) using 2 new rice lines and 2 varieties, namely Mekongga and Inpari 35 varieties. The number of treatments used in this study were 4 treatments with 4 replications. The number of experimental plots is 16 plots. The results showed that 2 new rice lines adapted to the vegetative and generative phases, i.e., line 1 had an effect on plant height (14 and 35 days after planting), number of tillers (14 days after planting and 35 days after planting) and flowering age (65 days after planting), and line 2 had an effect on productive tillers variable (12.9), 1000 grain weight (25.20) and ton/ha (4.60 kg). Keywords : Rice line, saline soil, adaptation